Kryteria identyczności a procedury indywidualizacyjne - Andrzejewski, Adam (Filozofia Nauki, 2009)
The main subject of the article is a critical analysis of the functions of the criteria of identity. The author presents a methodological stance called criterialism which claims that the criteria of identity play an important role and have a vast application in both science and philosophy. A set of arguments is presented then to show a polemic stance that the criteria of identity are not responsible for individuation. The author nevertheless acknowledges a positive function of the criteria of identity, which is stated under the name of ontological clarification.